Mid-Term Impact of Conduction System Pacing on Overall Cardiac Performance: A Non-Randomized, Prospective, Single-Center Echocardiographic Study - Catalin Pestrea; Ecaterina Cicala; Roxana Enache; Marcela Rusu; Radu Gavrilescu; Adrian Vaduva; Madalina Ivascu; Florin Ortan; Dana Pop (Diseases)
Introduction. Recently published data suggested significantly lower pacing-induced cardiomyopathy (PICM) incidence with conduction system pacing (CSP). Because most data evaluated only the impact on the left ventricle, this study aimed to assess changes in echocardiographic parameters of morphology and function for all heart chambers in patients with baseline preserved and mid-range LVEF over a medium-term follow-up period after CSP. Methods. A total of 128 consecutive patients with LVEF > 40% and successful CSP for bradyarrhythmic indication were prospectively enrolled. A complete 2D echocardiographic examination was performed at baseline and the last follow-up. Results. In total, 38 patients received His bundle pacing (HBP) and 90 received left bundle branch area pacing (LBBAP). The mean follow-up period was 699.2 ± 177.2 days, with 23 patients lost during this period. The ventricular pacing burden for the entire group was 97.2 ± 4.2%. Only three patients (2.9%) met the criteria for PICM. CSP led to a significant increase in LVEF (from 54.2 ± 7.9 to 56.7 ± 7.8%, p = 0.01) and a significant decrease in LV diastolic (from 107.2 ± 41.8 to 91.3 ± 41.8 mL, p < 0.001) and systolic (from 49.7 ± 21.4 to 39.5 ± 18.2 mL, p < 0.001) volumes. There were no significant changes in E/e′, mitral regurgitation, atrial volumes, and right ventricle (RV) diameter. There was a significant improvement in RV function. Tricuspid regurgitation was the only parameter that worsened. There were no differences in evolution for each echocardiographic parameter between the HBP and the LBBAP groups. Conclusions. HBP and LBBAP are equally protective for harmful changes in both atria and ventricles. The prevalence of PICM, defined as a decrease in LVEF, is very low with CSP.